Pedagogical aktiviti of professor V.E. Timonov (1862–1936) - Soloviova, L. M. (History of science and technology, 2018)
A talented scientist, engineer, popularizer of scitech V.E. Timonov, that left after itself considerable scientific works and whole pleiad of students, presents considerable interest and for pedagogical science. However, in the center of study of life and activity of scientist a scientific inheritance appeared, first of all, in industry of the hydraulic engineering and water-carriage, and question of him professionally-pedagogical activity until now were not the article of the special consideration. As all prominent teachers, Vsevolod Evgenievich left after itself not only scientific and pedagogical works but also main - the students and followers. The last, as a rule, recreate for us різноплановий character of the spiritually enriched man that owns encyclopaedic knowledge. All of it by the best character befits for V.E. Timonov.